Efektivitas Live Streaming Commerce dalam Meningkatkan Engagement dan Konversi Konsumen Generasi Z - Amanda Putri Setiawan; Dewa Putu Yudi Pardita; I Made Setena (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The advancement of digital technology has driven transformations in marketing strategies, including the rise of live streaming commerce that enables real-time interaction between sellers and consumers. This study aims to analyze the effectiveness of live streaming in increasing engagement and conversion among Generation Z in the fashion and accessories categories. A mixed-method approach was applied, combining qualitative interviews and observations with quantitative surveys and platform analytics. The results show that Shopee Live is more effective in driving purchase conversion through transactional features, while TikTok Live excels in building engagement and brand awareness. This research offers practical insights for businesses in designing digital marketing strategies aligned with platform characteristics and the preferences of young consumers. The study involved four key informants, shop owners who have more than 10,000 followers and actively live stream on Shopee and TikTok every day. In addition, an online survey was conducted with 120 people from Generation Z who have watched live streaming sessions on fashion and accessory products. The research was conducted thoroughly using qualitative and quantitative methods. The results provide a comprehensive overview of the effectiveness, engagement and conversion of both platforms.